2007
DOI: 10.1016/j.jnucmat.2007.01.164
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium retention in carbon fibre composites NB31 and N11 irradiated with low-energy D ions

Abstract: Plasma facing carbon fibre composites (CFC) are used for Tore Supra (CFC N11 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 16 publications
9
66
0
2
Order By: Relevance
“…It has been proposed that this di erence may be explained by deep di usion of D into carbon bre composite (CFC) material [32,33]. This deep di usion has been shown experimentally in laboratory experiments [34]. However, while at Tore Supra the whole CIEL limiter is made from CFC and exposes large CFC surfaces to the plasma, the use of CFC is limited to the inner strike point tile 4 in ASDEX Upgrade.…”
Section: Deuterium Inputmentioning
confidence: 99%
“…It has been proposed that this di erence may be explained by deep di usion of D into carbon bre composite (CFC) material [32,33]. This deep di usion has been shown experimentally in laboratory experiments [34]. However, while at Tore Supra the whole CIEL limiter is made from CFC and exposes large CFC surfaces to the plasma, the use of CFC is limited to the inner strike point tile 4 in ASDEX Upgrade.…”
Section: Deuterium Inputmentioning
confidence: 99%
“…Deuterium can penetrate in these materials up to depths of several tens to several hundreds of µm, where it is trapped at low concentrations [1,2]. It has been assumed that this deep penetration is an important process for the deuterium inventory in the tokamak Tore Supra [3], and it has been shown that deep penetration is dominating the remaining deuterium inventory in the all-tungsten tokamak ASDEX Upgrade [4].…”
Section: Introductionmentioning
confidence: 99%
“…The gas permeability of carbon materials probably explains the observed deep diffusion and deep trapping of deuterium in porous graphite materials [1]: Some hydrocarbon radicals and hydrogen molecules can penetrate deep into the material along the open porosity and then adsorb at the walls of the pore. …”
Section: Resultsmentioning
confidence: 99%
“…A deep diffusion of hydrogen into CFC was observed in laboratory experiments [1], and this deep diffusion and trapping inside the material might be responsible for the high D inventory observed in Tore Supra [2], where large areas of CFC material are exposed to the plasma at the CIEL limiter. The mechanism of deep tritium permeation in carbon-based materials is thought to be migration through open porosity.…”
Section: Introductionmentioning
confidence: 90%